Hidden role of the book Hovory s T. G. Masarykem - Opelík, Jiří (Bohemica Olomucensia, 2013)
The main role of the book Hovory s T. G. Masarykem was to mediate president's thoughts to the Czech nation and to show its moral background (i.e. the president's life and work). The book Hovory s T. G. Masarykem played another, very special role - the book influenced the birth and character of Čapek's crucial prose, so called "noetic trilogy". This fact fundamentally strenghten the position of the book Hovory s T. G. Masarykem in the context of Čapek's work.